The Role of Natural Killer Cells and Innate Lymphoid Cells in Immune Surveillance Against Cancer in Mice: A Review - Abd Alameer, Ali Mohammed; Najm, Asmaa Adnan (Journal of natural sciences, life and applied sciences, 2025)
T cells are essential components in cancer immunotherapy, scanning the body for antigens presented on MHC molecules to specifically target tumors. Cytotoxic Cluster of differentiation 8 (CD8+) CD8+ T cells and Th1 polarized Cluster of differentiation 4 (CD4+) CD4+ T cells are associated with better therapeutic outcomes. However, immune responses against cancer are not limited to conventional T cells but involve various immune cells crucial for early carcinogenesis. Many immune cells, despite lacking specific receptors for peptide antigens, can detect early signs of malignancy. Innate immune cells like macrophages and neutrophils provide immediate tumor protection. Unconventional T cells, including NKT and γδ T cells, and innate lymphoid cells (ILCs), further enhance immune surveillance. This diversity emphasizes the cooperative role of both conventional and innate immune cells in strengthening tumor monitoring, offering comprehensive protection in all stages of cancer development, from early malignant transformation detection to immunotherapy responses. The study aims to explore the pivotal roles of conventional and unconventional T cells and innate immune cells in early tumor detection and immune surveillance, aiming to improve immunotherapy effectiveness by understanding their complex interactions in early carcinogenesis.